2021
DOI: 10.3390/cancers13225599
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic KRAS: Signaling and Drug Resistance

Abstract: RAS proteins play a role in many physiological signals transduction processes, including cell growth, division, and survival. The Ras protein has amino acids 188-189 and functions as GTPase. These proteins are switch molecules that cycle between inactive GDP-bound and active GTP-bound by guanine nucleotide exchange factors (GEFs). KRAS is one of the Ras superfamily isoforms (N-RAS, H-RAS, and K-RAS) that frequently mutate in cancer. The mutation of KRAS is essentially performing the transformation in humans. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 82 publications
0
36
0
Order By: Relevance
“…K‐ras signaling is a well established pathway for oncogenic transformation. 52 Our data suggested that K‐ras signaling pathway upregulation was related to the acquisition of tumorigenic potential in high‐CIN cells. It was also suggested that inhibition of the K‐ras signaling pathway can be a strategy to eradicate CIN cancer cells.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…K‐ras signaling is a well established pathway for oncogenic transformation. 52 Our data suggested that K‐ras signaling pathway upregulation was related to the acquisition of tumorigenic potential in high‐CIN cells. It was also suggested that inhibition of the K‐ras signaling pathway can be a strategy to eradicate CIN cancer cells.…”
Section: Discussionmentioning
confidence: 59%
“…We also found that high‐CIN cells were specifically sensitive to the inhibitors of the K‐ras signaling pathway in 3D culture. K‐ras signaling is a well established pathway for oncogenic transformation 52 . Our data suggested that K‐ras signaling pathway upregulation was related to the acquisition of tumorigenic potential in high‐CIN cells.…”
Section: Discussionmentioning
confidence: 61%
“…Our results showed that the high-risk group was mainly involved in unfolded protein response, DNA repair signaling, and epithelial-mesenchymal transition signaling pathway and glycolysis pathway (Figures 7(a) – 7(d) ), which are related to the initiation of metastasis in cancer progression [ 18 20 ]. The low-risk group was mainly involved in estrogen response early and KRAS signaling pathway (Figures 7(e) and 7(f) ), which are important for oncogene of osteosarcoma [ 21 , 22 ]. These results indicated that there were differences in biological characteristics between high-risk and low-risk groups, which affected tumorigenesis and progression of osteosarcoma and survival of osteosarcoma patients.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the results reported in Figure 4 let us conclude that exposing GO to the plasma of NOP, PDAC, and breast cancer patients lead to personalized coronas of significantly different protein composition. According to the literature, we can speculate that these differences may be the consequence of alterations in the human proteome, resulting from mutations of genes that are known to be involved in the processes of carcinogenesis for both pancreatic and breast cancer (e.g., K-RAS and BRCA) [32]. Nonetheless, it has been recently reported that altered protein profiles in pancreatic and breast cancer occur and most of these proteins are involved in amino-acid, lipids, monosaccharides, and sulfur compound synthesis and metabolism [33].…”
Section: Discussionmentioning
confidence: 99%